Synthesis of Self-Assembled and Hierarchical Palladium-Cnts-Reduced Graphene Oxide Composites for Enhanced Field Emission Properties - Singh, D (Elsevier Ltd, 2017)
We report the synthesis of palladium-graphene oxide based (Pd-rGO) composite and its enhanced electron field emission studies. The palladium nanoparticles decorated reduced graphene oxide (Pd-NPs-rGO) and Pd catalyst assisted grown CNTs on reduced graphene oxide (Pd-CNTs-rGO) composite have been synthesized employing microwave. The hierarchical Pd-CNTs-rGO composite shows enhanced field emission performance due to the synergestic effect of Pd catalyst assisted grown CNTs on rGO nanosheets (rGO-NSs) and its proper contact on rGO surfaces. The enhanced field emission behavior of Pd-CNTs-rGO composite is attributed to the easy electron tunneling from the one-dimensional CNTs, which increases the emission sites and hence the field emission current density. The Pd-CNTs-rGO composite exhibits lower turn-on field, lower threshold field, larger field enhancement factor and high emission current stability as compared to Pd-NPs-rGO composite. © 2017 Elsevier Ltd